UPAYA MENINGKATKAN KENYAMANAN KELAS C DALAM TINJAUAN ARSITEKTURAL GUNA MENDUKUNG PROSES BELAJAR MENGAJAR TARUNA AKMIL - Naufal Rafi Pradya; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (PPM Sdirjianbang Akademi Militer, 2023)
The Military Academy is an educational institution located in the City of Magelang, Central Java. The facilities provided at educational institutions are very diverse, including class buildings, one of which is the Class C building, in the Class C building there are classrooms for cadets to carry out teaching and learning activities. In order to increase the comfort of Military Academy Cadets in carrying out teaching and learning activities. There are several indicators, namely temperature, lighting, and air circulation. Where the indicators above are found in the classroom facilities in Building C of the Military Academy. The purpose of this study was to analyze the condition of the C class building based on these indicators, as well as obtain solutions to increase the comfort of the class C building when it is used for teaching and learning activities. This research is a quantitative research. The source of data in this study is primary data obtained through data collection by distributing questionnaires to respondents, namely Cadets TK II and TK III. Meanwhile, secondary data comes from literature and journals that support the completion of this Final Project. The results of this study are that the condition of the Class C building is in good condition when used to carry out the teaching and learning process, but optimization is still needed so that it can increase the comfort of cadets in carrying out teaching and learning activities carried out in the classrooms of Building C.